2017
DOI: 10.4172/2252-5211.1000296
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Organic Wastes for Sustainable Soil Health and Crop Growth

Abstract: IntroductionA variety of wastes generated through different agricultural and other activities in our day to day life including crop residues in the form of straw, stover, husk, biomass of uncultivated plant species and weeds, forest biomass; animal wastes and by products like dung, urine, bones, fish processing wastes and human habitation wastes like garbage, sewage and sludge etc. (Table 1). Crop residues are abundantly generated in large quantities during crop cultivation. After harvesting the economic part(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Sustaining an adequate soil organic matter content plays an important role in maintaining and improving soil microbial health and soil structure, which is crucial for attaining sustainable crop production (Chatterjee et al 2017). Moreover, European policy has recognised soil organic carbon (SOC) as an instrument to reduce CO 2 emission through soil C sequestration (Lugato et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sustaining an adequate soil organic matter content plays an important role in maintaining and improving soil microbial health and soil structure, which is crucial for attaining sustainable crop production (Chatterjee et al 2017). Moreover, European policy has recognised soil organic carbon (SOC) as an instrument to reduce CO 2 emission through soil C sequestration (Lugato et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tayebeh et al [26] reported that about 30% of the required N fertilizer can be replaced by organic fertilizers, because organic fertilizer application improved N use efficiency, compared with the sole application of chemical fertilizers. Chatterjee et al [27] also reported that the integrated use of chemical and organic (green manure) fertilizers can save 50-75% of the required N fertilizers in rice as well as increasing the availability of several other plant nutrients through its positive effects on various soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…The progressive increase in net energy with OF as compared to CF was due to yield improvement with the former practice. This might be attributed to progressive yield improvement under organic farming (Schrama et al, 2018) due to a beneficial residual effect of OF in improving soil physico-chemical properties (Chatterjee et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, in the African continent reported annual losses include 22, 2.5 and 15 kg ha −1 of N, P and K, respectively (Hilhorst et al, 2003). Considering these, the organic waste recycling for plant nutrient supply is essential for replenishment of plant nutrients, sustaining soil health, reducing the pollution problem, and creating employment opportunities (Chatterjee et al, 2017; Dreschel and Kunze, 2001; Solano et al, 2001). The National Mission for Sustainable Agriculture in India is engaged in enhancing agricultural productivity, especially in rainfed areas focusing on integrated farming, water use efficiency, soil health management and resource conservation with emphasis on agriwaste recycling.…”
Section: Introductionmentioning
confidence: 99%